The chief information officer's body of knowledge : people, process, and technology - Lane, Dean. (Hoboken, N.J. : John Wiley & Sons, 2011)
'A contributed volume, this book was written by practitioners who handle both the day-to-day and longer term challenges that Information Technology (IT) departments and their parent businesses face. It is a hands-on, practical application, IT desk reference written in lay terms for business people and IT personnel alike. There are no lofty theories or references to hypotheses. This is a book that will help individuals understand how to assist companies establish standard practices so they may become more effective and efficient. It provides guidance on how a business person and IT can work together to maximize business value. It also addresses the Chief Information Officer managing and running IT as a business so that the IT department may become a full strategic partner in the organization's crucial decisions'--Provided by publisher.
Includes index.
Keywords: Information technology -- Management; Chief information officers